DAYA TARIK PURA PARAHYANGAN JAGATKARTA SEBAGAI WISATA BUDAYA DI KABUPATEN BOGOR - Setiawan, Aditya Sugih; Batubara, Rima Pratiwi (STABN Raden Wijaya Wonogiri, 2023)
As one of the tourist attractions in Bogor Regency, Pura Parahyangan Agung Jagatkarta is the largest temple in West Java and the second largest in Indonesia after Besakih Temple in Bali. The lack of tourist attractions and promotions is considered to be the thing that causes tourism activities in the area to be not optimal. The study was conducted with a quantitative approach to assess tourist attractiveness in terms of something to see, something to do, and something to buy. The aspect of something to see achieves a tourist response, which is 83.2%. The something to do aspect is 78.6% and the something to buy aspect is 76.4%. All three aspects get good marks so that the tourist attraction of Pura Parahyangan Agung Jagatkarta is not problematic in terms of tourist attractions